Venom gland transcriptomic and venom proteomic analyses of the scorpion Megacormus gertschi Díaz-Najera, 1966 (Scorpiones: Euscorpiidae: Megacorminae). (July 2017) - Santibáñez-López, Carlos E.; Cid-Uribe, Jimena I.; Zamudio, Fernando Z.; Batista, Cesar V.F.; Ortiz, Ernesto; Possani, Lourival D.
Abstract: The soluble venom from the Mexican scorpion Megacormus gertschi of the family Euscorpiidae was obtained and its biological effects were tested in several animal models. This venom is not toxic to mice at doses of 100 μg per 20 g of mouse weight, while being lethal to arthropods (insects and crustaceans), at doses of 20 μg (for crickets) and 100 μg (for shrimps) per animal. Samples of the venom were separated by high performance liquid chromatography and circa 80 distinct chromatographic fractions were obtained from which 67 components have had their molecular weights determined by mass spectrometry analysis. The N-terminal amino acid sequence of seven protein/peptides were obtained by Edman degradation and are reported. Among the high molecular weight components there are enzymes with experimentally-confirmed phospholipase activity. A pair of telsons from this scorpion species was dissected, from which total RNA was extracted and used for cDNA library construction. Massive sequencing by the Illumina protocol, followed by de novo assembly, resulted in a total of 110, 528 transcripts. From those, we were able to annotate 182, which putatively code for peptides/proteins with sequence similarity to previously-reported venom components available from different protein databases. Transcripts seemingly coding for enzymes showed the richest diversity, with 52 sequences putatively coding for proteases, 20 for phospholipases, 8 for lipases and 5 for hyaluronidases. The number of different transcripts potentially coding for peptides with sequence similarity to those that affect ion channels was 19, for putative antimicrobial peptides 19, and for protease inhibitor-like peptides, 18. Transcripts seemingly coding for other venom components were identified and described. The LC/MS analysis of a trypsin-digested venom aliquot resulted in 23 matches with the translated transcriptome database, which validates the transcriptome. The proteomic and transcriptomic analyses reported here constitute the first approach to study the venom components from a scorpion species belonging to the family Euscorpiidae. The data certainly show that this venom is different from all the ones described thus far in the literature. Highlights: Results of proteome analysis of venom and transcriptome analysis of venom gland from M. gertschi scorpion are reported. This venom is not toxic to mammals but is lethal to arthropods (crickets and shrimps) at the doses assayed. HPLC separation permitted identification of 67 components, from which 30 distinct protein/peptide components were found. Sequences found are: enzymes, toxins, non-disulfide bridged peptides, scorpines, La1-like peptides and other components. Over 50% of the whole soluble venom is made of low molecular weight non-peptide/protein components, of unknown function.